Scale space has been discovered in Japan - Weickert, Joachim 1965-; Ishikawa, Seiji; Imiya, Atsushi (1997)
Abstract: "Gaussian scale-space is considered to be a modern bottom-up tool in computer vision. The American and European vision community, however, is unaware of the fact that Gaussian scale-space has already been axiomatically derived in 1959 in a Japanese paper by Taizo Iijima. This result formed the starting point of an entire world of linear scale-space research in Japan ranging from various axiomatic derivations over deep structure analysis to applications to optical character recognition (OCR). Since this world is unknown to western scale-space researchers and many papers are written in Japanese, we give an overview of the basic concepts. In particular, we review four Japanese axiomatics for Gaussian scale-space which have been proposed between 1959 and 1981. By juxtaposing them to ten American or European axiomatics, we present an overview of the state-of-the-art in Gaussian scale-space axiomatics."
Keywords: Mathematik; Computer vision; Gaussian processes; Image processing -- Mathematics; Optical pattern recognition